The product of the slope of two perpendicular lines is -1. The slope of the line y = (-1/4)x + 4 is (-1/4), a line perpendicular to this line has a slope of 4.
As the required line passes through the point (-1, 3)
(y - 3)/(x + 1) = 4
=> y - 3 = 4x + 4
=> 4x - y + 7 = 0
The equation of the line perpendicular to y = (-1/4)x + 4 and passing through the point (-1, 3) is 4x - y + 7 = 0
because they are perpendicular the slope of the line is 4.
let's call the slope of the first line is m1 (which is -1/4) and the slope of the second line is m2 (which is 4)
we know that this line (the second one) passes through (-1,3)